Multimedia over CDMA mobile wireless networks: A joint source coding -power control approach - Chan, Yee Sin (ProQuest Dissertations & Theses, 2002)
We study the resource allocation problems in future third/fourth-generation (3G/4G) wireless CDMA cellular networks supporting heterogeneous multimedia traffic with diverse end-user quality-of-service (QoS) requirements. We investigate transport schemes for maximizing the number of users that can be supported in a single cell while simultaneously maximizing the end-user, application-specific QoS of individual users. More specifically, we demonstrate that the network resources consumed by an individual user in a spread-spectrum CDMA network can be taken as the product of the allocated source coding rate, Rs, and the energy per bit normalized to the multiple-access interference noise density, Eb/N 0. We propose a joint source coding and power control (JSCPC) approach for allocating these two quantities to an individual user, subject to a constraint on the total available bandwidth, to simultaneously maximize the per-cell capacity while maximizing the QoS delivered to individual users. This JSCPC approach is developed first for a single-layer video delivery system and later extended for multi-layer video delivery over mobile wireless CDMA networks. We demonstrate the efficacy of this approach using the ITU-T H.263+ video source codes, although the approach is generally applicable to other source coding schemes as well. The results indicate a significant improvement in delivered QoS, measured in terms of the end-user average PSNR, that can be achieved at a given level of network loading. Furthermore, we demonstrate that without an appropriate JSCPC procedure the traditional soft-capacity limit associated with CDMA networks is no longer present. Indeed, a precipitous decrease in performance can be expected with increasing load. We show that this behavior can be avoided with the proposed JSCPC procedure thereby significantly extending the useful capacity of the CDMA network while exhibiting a more graceful degradation pattern under increasing load. We also address joint source-channel coding (JSCC) approaches in spread-spectrum CDMA systems. More specifically, we consider using the class of rate-compatible punctured convolutional/turbo (RCPC/RCPT) codes in conjunction with the JSCPC methodology for video transport over spread-spectrum networks. Results indicate that there is substantial gain in system performance by employing this JSCC/JSCPC approach. Finally, we propose an end-to-end embedded approach for multicast/broadcast of digital video over CDMA mobile wireless networks. In particular, we consider the use of nonuniform MPSK in tandem with a JSCC/JSCPC approach employing the class of rate-compatible punctured turbo (RCPT) codes. We show the superiority of this embedded transmission scheme for multicast/broadcast of multimedia services in mobile wireless environment. More specifically, we demonstrate an enhanced end-video quality can be achieved using the proposed scheme for more capable receivers while providing a basic video-quality for less capable receivers.